Data Underpinning "Weld-Bonded Stainless Steel to Carbon Fibre-Reinforced Plastic Joints" - Colegrove, Paul; Joesbury, Adam; Ayre, David; Van Rymenant, Patrick; Ganguly, Supriyo; Williams, Stewart W. (Cranfield University, 2017)
Figures for article entitled "Weld-Bonded Stainless Steel to Carbon Fibre-Reinforced Plastic Joints"
Keywords: 'Composite materials'; 'metals'; 'joining'; 'CFRP'; 'spot-welding'; 'weld-bonding'; 'Aerospace Materials'; 'Aerospace Structures'; 'Materials Engineering not elsewhere classified'; 'Polymers and Plastics'; 'Metals and Alloy Materials'